Neutralization of TSLP inhibits airway remodeling in a murine model of allergic asthma induced by chronic exposure to house dust mite. - Zhuang-Gui Chen; Tian-Tuo Zhang; Hong-Tao Li; Fen-Hua Chen; Xiao-Ling Zou; Jing-Zhi Ji; Hong Chen (PLoS ONE, 2013)
Chronic allergic asthma is characterized by Th2-typed inflammation, and contributes to airway remodeling and the deterioration of lung function. However, the initiating factor that links airway inflammation to remodeling is unknown. Thymic stromal lymphopoietin (TSLP), an epithelium-derived cytokine, can strongly activate lung dendritic cells (DCs) through the TSLP-TSLPR and OX40L-OX40 signaling pathways to promote Th2 differentiation. To determine whether TSLP is the underlying trigger of airway remodeling in chronic allergen-induced asthma, we induced allergic airway inflammation in mice by intranasal administration of house dust mite (HDM) extracts for up to 5 consecutive weeks. We showed that repeated respiratory exposure to HDM caused significant airway eosinophilic inflammation, peribronchial collagen deposition, goblet cell hyperplasia, and airway hyperreactivity (AHR) to methacholine. These effects were accompanied with a salient Th2 response that was characterized by the upregulation of Th2-typed cytokines, such as IL-4 and IL-13, as well as the transcription factor GATA-3. Moreover, the levels of TSLP and transforming growth factor beta 1 (TGF-β1) were also increased in the airway. We further demonstrated, using the chronic HDM-induced asthma model, that the inhibition of Th2 responses via neutralization of TSLP with an anti-TSLP mAb reversed airway inflammation, prevented structural alterations, and decreased AHR to methacholine and TGF-β1 level. These results suggest that TSLP plays a pivotal role in the initiation and persistence of airway inflammation and remodeling in the context of chronic allergic asthma.